KANDUNGAN FITOKIMIA DAN NILAI SUN PROTECTION FACTORS (SPF) PADA EKSTRAK METANOL Hypnea pannosa, Turbinaria decurrens, DAN Caulerpa serrulata. (PHYTOCHEMICAL CONTENT AND VALUE OF SUN PROTECTION FACTORS (SPF) IN METHANOL EXTRACTS OF Hypnea pannosa, Turbinaria decurrens, AND Caulerpa serrulata) - Dewi Kartika Putri; Nora Idiawati; Mega Sari Juane Sofiana (Tanjungpura University, 2022)
Seaweed grows abundantly in Indonesian waters. Seaweed is an important commodity and valuable for the cosmetic industry. The aim of this research was to determine the phytochemical content and SPF value of the methanol extract of seaweeds, namely Caulerpa serrulata, Turbinaria decurrens, and Hypnea pannosa. The sample was macerated with methanol solvent. The methanol extract of C. serrulata obtained the highest yield of 4.42 g. The results of phytochemical screening on C. serrulata, T. decurrens, and H. pannosa contains alkaloids, flavonoids, terpenoids, tannins, and saponins. The SPF of methanol extract was analyzed by UV-Vis Spectrophotometer. SPF values with a concentration of 100 ppm were obtained for C. serrulata (4.80), T. deccurens (0.81), and H. pannosa (0.80). The methanol extract from C. serrulata was the highest SPF. It was categorized in the moderate protection category.